How many people living with HIV will be additionally eligible for antiretroviral treatment in Karnataka State, India as per the World Health Organization 2013 guidelines? - Sunil Kumar Dodderi; Ajay M V Kumar; Balaji R Naik; Avinash Kanchar; Rewari B B; Anthony D Harries (PLoS ONE)
Background The National AIDS control programme (NACP) in India is currently following the World Health Organization (WHO) 2010 antiretroviral therapy (ART) guidelines. In 2013, the WHO revised its recommendations for initiating ART among people living with HIV (PLHIV) by increasing the threshold for ART initiation to a CD4 count ≤500 cells/uL. For certain patient groups, ART is recommended irrespective of CD4 count (PLHIV with active tuberculosis, hepatitis B virus infection, pregnant and breast feeding women, children aged under five years and those living in a sero-discordant relationship). In this operational research, we assess the effect of applying this recommendation on the number of PLHIV additionally eligible for ART. Methods This was a cross-sectional analysis of routinely collected programme data from all PLHIV registered in Karnataka State (population 60 million), India in 2012. Results Of 37,044 PLHIV, 27,074 (73%) were eligible for initiating ART as per WHO-2010 criteria. As per the WHO-2013 criteria (CD4 count ≤500 and all pregnant women and under-five children irrespective of CD4 count), an additional 5104 (14%) HIV-infected people would be eligible for initiating ART. There were no data to inform the additional patient load due to sero-discordance. Conclusion Adopting the WHO-2013 guidelines for India has important resource implications. However, given the significant patient and programmatic benefits of adopting the new guidelines, this has been considered favourably by the NACP in India and steps are being planned to integrate ART care into the general health system to cope with the increased numbers of patients.